Effect of Heat Treatment on Electrical Insulation of Strain Sensors for Aluminum Cast Parts - Marco Cen-Puc; Tim de Rijk; Dirk Lehmhus; Walter Lang (Proceedings)
This work presents the effect of thermal treatment on the electrical insulation of strain sensors on aluminum substrates. The sensors are meant to be embedded into cast aluminum parts, which are heat-treated for strengthening via precipitation hardening. For sensor manufacturing, thick film materials are used for the electrical insulation and its connection tracks, whereas sensing platinum structures are produced by sputtering. The effectiveness of different insulation thicknesses was tested for a treatment regime of 7 h at 535 °C, which matches solution heat treatment conditions as the most demanding part of the precipitation hardening process. The results showed that insulation is partially lost after treatment, and six consecutive insulating layers are required to produce an insulation capable of withstanding an extended heat treatment.